Cytokine Profiles Induced by the Novel Swine-Origin Influenza A/H1N1 Virus: Implications for Treatment Strategies - Woo, Patrick C. Y. (J Infect Dis, 2010)
Background. Given the apparent high mortality associated with the novel swine-origin influenza A/H1N1 virus (S-OIV) in Mexico, we aimed to study the cytokine profiles induced by S-OIV and the effect of immunomodulators. Methods. We assayed cytokines and their messenger RNA (mRNA) levels in culture supernatants of human macrophages infected with H5N1, S-OIV California/04/2009 (S-OIV-CA), S-OIV Hong Kong/415742 (S-OIV-HK), or seasonal H1N1 with or without celecoxib and mesalazine. Results. Among the 12 cytokines showing detectable levels, levels of 8 proinflammatory cytokines (interleukin [IL] 2R, IL-6, interferon [IFN] α, macrophage inflammatory protein [MIP] α, MIP-1b, IFN-induced protein 10, regulated on activation, normal T cell expressed and secreted [RANTES], and monocyte chemotactic protein [MCP] 1) were higher in cells infected by H5N1 but similar among cells infected with H1N1, S-OIV-CA, or SOIV- HK. The levels of the other 4 cytokines were similar for H5N1, H1N1, S-OIV-CA and S-OIV-HK. Among the 8 cytokines induced by H5N1, 6 were suppressed by celecoxib and mesalazine. The mRNA levels of tumor necrosis factor a, IFN-γ, IL-6, and MCP-1 induced by H5N1 were higher than the levels of other cytokines at 12 and/or 24 h. Conclusions. No major cytokine storm, as seen in H5N1 infection, is associated with S-OIV infection of cell lines. The mainstay of treatment for uncomplicated S-OIV infections should be antiviral agents without immunomodulators. For individual S-OIV-infected patients with severe primary viral pneumonia, severe sepsis, and multiorgan failure, immunomodulators may be considered as an adjunctive therapy in clinical trials.